Management of postprandial glucose: Recommended targets and treatment with biphasic insulin - Liebl, Andreas (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2016)
• Post-meal hyperglycaemia can predict the development of complications. • While causality is not proven, any link with cardiovascular disease is of concern. • Optimal management should thus include postprandial plasma glucose (PPG) levels. • Biphasic insulins provide similar overall and PPG control to basal–bolus therapy. • Biphasic insulins are a convenient alternative to basal–bolus therapy.